MITOCHONDRIAL FUNCTION IN SEPSIS. Issue 3 (March 2016) - Arulkumaran, Nishkantha; Deutschman, Clifford S.; Pinsky, Michael R.; Zuckerbraun, Brian; Schumacker, Paul T.; Gomez, Hernando; Gomez, Alonso; Murray, Patrick; Kellum, John A.
Abstract : ABSTRACT: Mitochondria are an essential part of the cellular infrastructure, being the primary site for high-energy adenosine triphosphate production through oxidative phosphorylation. Clearly, in severe systemic inflammatory states, like sepsis, cellular metabolism is usually altered, and end organ dysfunction is not only common, but also predictive of long-term morbidity and mortality. Clearly, interest is mitochondrial function both as a target for intracellular injury and response to extrinsic stress have been a major focus of basic science and clinical research into the pathophysiology of acute illness. However, mitochondria have multiple metabolic and signaling functions that may be central in both the expression of sepsis and its ultimate outcome. In this review, the authors address five primary questions centered on the role of mitochondria in sepsis. This review should be used both as a summary source in placing mitochondrial physiology within the context of acute illness and as a focal point for addressing new research into diagnostic and treatment opportunities these insights provide.